Penerapan Model Pembelajaran Quiz Team Untuk Meningkatkan Hasil Belajar Ekonomi Peserta Didik Kelas XI IPS 2 SMAN 8 Kediri Di Semester Ganjil Tahun Pelajaran 2018/2019 - Rochana Ulfiati Fadilah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2019)
Economic Learning in SMAN 8 Kediri specifically in class XI IPS 2, so far it is still being agreed by the teacher. The student's questioning activity is still low. Mostly, students do not understand the concepts and the interrelationships between economic concepts. The researcher chose the Quiz Team learning method. Researchers chose the Quiz learning model because learning with the opinion of Silberman. The Quiz Team is a technique to increase participants' responsibility for what they do in a fun and non-scary way. This active learning type of Quiz Team is a technique to increase the responsibility of students towards what they improve through fun and non-frightening ways. In this study, researchers used the action research design model Kemmis and Mc. In the research design there are four stages of research namely planning (planning), action (implementation), observation (observing) and reflection (reflection). In cycle 1, researchers divided 3 large groups, A, B, and C, each group consisting of 11 students. The researcher chooses three topics which will be presented in three segments. The results of the study increased the number of students who achieved minimal completeness in each cycle. In cycle 2, researchers divided the group into smaller ones, in cycle II there were 6 groups, A, B, C, D, E and F. In cycle II, researchers divided into 6 national income calculation concepts namely the concept: Gross Domestic Product (GDP), Gross National Product (GNP), Net National Product (NNP), Net National Income (NNI), Personal Income (PI), Disposible Income (DI). Indicators Success in improving student learning outcomes in this study was seen from 80% of students completing KKM (with a value of 77). The results of the study increased the number of students who achieved minimal completeness in each cycle. At the 42% level (14) students complete KKM. In cycle 1 Approximately 61% (20) of students have completed KKM. In cycle 2, around 82% or 26 students completed KKM. The data has increased from pre-cycle to cycle 2. Keywords: Learning Outcomes, Class XI IPS 2, National Revenue, Quiz Team.